Controlling Financial Risks’ Impact on Accounting Information Quality: Evidence from Iraqi banks - Abd Oun, Safaa Jabbar; Abdulhussein , Azher Subhi (Technium Social Sciences Journal, 2024)
Controlling risk management strategies and implementing preventive actions are essential for creating a secure and conducive environment for individuals and organisations. The study aims to showcase the influence of financial risk control on the quality of accounting information in Iraqi banks. This will be achieved by identifying and assessing risks, as well as designing and implementing suitable procedures to manage hazards. The goal is to produce reliable accounting information that stakeholders can trust. The study employed 154 questions that were delivered to accountants, internal auditors, external auditors, and academics specialising in Iraqi institutions. It consisted of two axes. The initial objective was to evaluate the management of financial risk control in Iraqi banks. The first axis comprised 17 specific questions, while the second axis assessed the accuracy of its accounting information and consisted of 21 questions. The study variables were assessed utilising the statistical software SPSS version 26, while the hypotheses were examined by simple linear regression. The study found that implementing robust procedures and policies to manage financial risks in banks improves the reliability and transparency of their accounting information. This includes effectively addressing various risks, such as geopolitical concerns.